Cognitive Mapping and Class Consciousness: A Comparative Analysis of Saba Imtiaz’s Karachi, You’re Killing Me! and Kamila Shamsie’s Kartography - Amber Kamran; Harmain Rukh (NUML Journal of Critical Inquiry)
This research explores the concept of cognitive mapping and underlines the challenge of class consciousness and its effects on the mental maps. Nuanced with subjective mappings, literature lacks comprehensive depictions of lived and navigated space. This study examines two Pakistani novels, Saba Imtiaz’s Karachi, You're Killing Me! and Kamila Shamsie’s Kartography, by using the theoretical framework of cognitive mapping proposed by Frederick Jameson. The comparative analysis reveals the subjective implications of the protagonists' social statuses in both texts. It highlights how different class structures map the same space and location in accordance with their respective social contexts. It also analyses the subjectivity of the depictions and the erroneous nature of city maps depicted in literary works in a way that not every faction of the society can relate to it.